Condensins Promote Coorientation of Sister Chromatids During Meiosis I in Budding Yeast - Brito, Ilana L. (Genetics Society of America, 2010)
The condensin complex is a key determinant of higher-ordered chromosome structure. We show here that the complex is also important for the correct alignment of chromosomes on the meiosis I spindle. Unlike during mitosis and meiosis II, when sister chromatids attach to microtubules emanating from opposite spindle poles (biorientation), accurate meiosis I chromosome segregation requires that sister chromatids attach to microtubules emanating from the same spindle pole (coorientation). The monopolin complex, consisting of Lrs4, Csm1, and the meiosis-specific component Mam1, brings about meiosis I coorientation. We find that in the absence of functional condensin complexes, a fraction of sister kinetochores biorient on the meiosis I spindle and association of the monopolin complex subunit Mam1 with kinetochores is decreased. Our studies uncover a new locus-specific effect of the condensin complex.